MANUFACTURE OF LIGNINOLYTIC FUNGI INOCULUM Geotrichum sp. WITH SORGUM (Sorghum bicolor) MEDIA AND ITS EFFECT ON THE QUALITY OF BAMBOO LEAF COMPOST (Bambusa sp.) - Nadya Febri Harlifia; Bambang Irawan; Salman Farisi; Suratman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Bamboo is a type of plant that grows in Indonesia. So far, people only use the stems and throw away the leaves. As a result, these abundant bamboo leaves become waste. Bamboo leaf waste contains lignin content of 19.8-26.6%, and becomes compost in the long term. The process of composting bamboo leaf litter can be accelerated using an activator such as the inoculum fungi Geotrichum sp. which is ligninolytic so that it can break down lignin complex compounds contained in bamboo leaf waste into simpler compounds. Sorghum contains about 6.5-7.9% fiber. The high fiber content in sorghum seeds can be used as a growth medium for fungal inoculum. The purpose of this study was to determine the effect of sorghum as an inoculum medium for Geotrichum sp. and the effect of inoculum on compost quality. This research was carried out in August - December 2019 at the Microbiology Laboratory of the Biology Department, Faculty of Mathematics and Natural Sciences, Unila. This study used a completely randomized design (CRD) method with 4 treatments, namely Control (Bamboo leaf litter), P1 (Bamboo leaf litter + 1% inoculum), P2 (Bamboo leaf litter + 1.5 % inoculum) and P3 (Bamboo leaf litter). + 2% inoculum) each treatment was repeated 3 times. The variables observed were the number of spores and spore viability using the Colony Forming Unit (CFU) calculation on inoculum and compost. Analysis of the content of C, N, P, and C/N ratio was carried out to determine the quality of the compost. Based on the research results, sorghum can be used as a growth medium for the ligninolytic fungi inoculum Geotrichum sp. with spore viability of 74.18% and the addition of 1.5% inoculum (P2) gave the best results on the quality of bamboo leaf compost (Bambusa sp.)